Optimal Growth with Robust Feedback Control - Infante, Ettore F.; Stein, Jerome L. (Review of Economic Studies, 1973)
Ettore F. Infante, Jerome L. Stein; Optimal Growth with Robust Feedback Control12, The Review of Economic Studies, Volume 40, Issue 1, 1 January 1973, Page